Tactile Drawings, Ethics, and a Sanctuary: Metaphoric Devices Invented by a Blind Woman. (June 2013) - Kennedy, John M
Until the last two decades, indications that blind people would understand and create pictures were sparse. EW, a totally blind adult, who began making raised-line drawings in her thirties, created a portfolio of several hundred sketches in nine years. She selects her own topics and invents her treatments of the subjects. What is of special interest here is that two of her drawings, shown in the present paper, depict places but also use devices to indicate one is a sanctuary and the other concerns a tragic era, using metaphor. Lightness of line in a forest drawing indicates it is out of reality, enchanted, and a sanctuary. A tilted grid in a drawing of a Holocaust memorial shows the events at issue were twisted and crooked. The devices are metaphoric and novel. The drawings deal with an ontological category—values—for which metaphorical devices in raised-line depictions have not previously been considered.